Pregnancy outcomes of mothers with very advanced maternal age (40 years or more) - Traisrisilp K. (Medical Association of Thailand, 2015)
© 2015, Medical Association of Thailand. All rights reserved. Objective: To assess pregnancy outcomes in women at age of 40 years or more compared with those at age of 20 to 30 years Material and Method: The retrospective cohort study was conducted at Maternal Fetal Medicine unit, Chiang Mai University Thailand, to identify the delivery. All consecutive records between January 2002 and December 2012 were searched. Singleton pregnancies with maternal age of 20 years or older were recruited for study. The primary outcomes for comparison were the rates of various obstetric outcomes, such as preterm birth, cesarean section, etc. Results: During the study period, 797 women at age of 40 years or more and 18,802 women at age of between 20 and 30 years were recruited. Women in the study group had significantly higher rates of medical diseases, such as chronic hypertension or pregestational diabetes mellitus. Cesarean rate, preterm delivery, and fetal growth restriction were significantly higher in the study group. Conclusion: Maternal age of 40 years or more is associated with medical complications and more operative deliveries. Furthermore, very advanced maternal age is significantly associated with adverse perinatal outcomes such as abortion, preterm birth, and fetal growth restriction. This information may be useful for obstetric counseling.